Duncan Dancer An Autobiography (Wesleyan University Press, 1966)
Born Irma Dorette Henriette Erich-Grimme (1897-1977), in Hamburg, Germany, Irma was one of six young girls, later called the Isadorables, taken in by Isadora Duncan. All six girls took Duncan's legally. Thus was born: Irma Duncan. Duncan Dancer is a valuable resource, describing her early career with Isadora Duncan and the Isadorables, through her time as a teacher taking students on tours to perform throughout the world. Today, many of her letters, photographs, notebooks, programs, clippings from newspapers and magazines, and other materials now form the Irma Duncan Collection, one of the most precious holdings of the New York Public Library's Dance Division.